Impact of Hospital-Employed Physician Assistants on a Level II Community-Based Orthopaedic Trauma System. (December 2016) - Althausen, Peter L.; Shannon, Steven; Owens, Brianne; Coll, Daniel; Cvitash, Michael; Lu, Minggen; O'Mara, Timothy J.; Bray, Timothy J.
Abstract : Objectives: The American Academy of Orthopedic Surgeons and the Orthopedic Trauma Association have released guidelines for the provision of orthopedic trauma services such as adequate stipends, designated operating rooms, ancillary staff, and guaranteed reimbursement for indigent care. One recommendation included a provision for hospital-based physician assistants (PAs). Given current reimbursement arrangements, PA collections for billable services may not meet their salary and benefit expenses. However, their actions may indirectly affect emergency room, operating room, and hospital reimbursement and patient care itself. The purpose of our study is to define the true impact of hospitalbased PAs on orthopaedic trauma care at a level II community hospital. Design: Retrospective case series. Setting: Level II trauma center. Patients/Participants: One thousand one hundred four trauma patients with orthopaedic injuries. Intervention: PA involvement. Main Outcome Measurements: Emergency room data such as triage time, time until seen by the orthopedic service, and total emergency room time was recorded. Operating room data such as time to surgery, set-up time, total operating time, and out of room time was entered as well. Charts were reviewed to determine if patients were given postoperative antibiotics and Deep Venous Thrombosis (DVT) prophylaxis. Intraoperative and postoperative complications were noted, and lengths of stay were calculated for all patients. Results: At our institution, PA collections from patient care cover only 50% of their costs for salary and benefits. However, with PA involvement, trauma patients with orthopedic injuries were seen 205 minutes faster (P = 0.006), total Emergency Room (ER) time decreased 175 minutes (P = 0.0001), and time to surgery improved 360 minutes (P . 0.03). Operating room parameters were minimally improved, but postoperative DVT prophylaxis increased by a mean of 6.73% (P = 0.0084), postoperative antibiotic administration increased by 2.88% (P = 0.0302), and there was a 4.67% decrease in postoperative complications (P = 0.0034). Average length of stay decreased by 0.61 days (P = 0.27). Conclusions: Although the PA's collections do not cover their costs, the indirect economic and patient care impacts are clear. By increasing emergency room pull through and decreasing times to Operating Room (OR), operative times, lengths of stay, and complications, their existence is clearly beneficial to hospitals, physicians, and patients as well. Level of Evidence: Economic Level IV. See Instructions for Authors for a complete description of levels of evidence.